VIJNANANIDHI CHIKITSA MANJARI - THE MANUSCRIPT TREASURE OF INDIA- A BIRDS EYE VIEW - Nanda, G.C. (International Journal of Ayurveda and Pharma Research, 2016)
Chikitsa Manjari a Palm leaf manuscript of Odisha preserved in Odisha state museum Bhubaneswar has got the national importance by Govt. of India as National Heritage which bears a great importance of its kind & nature. There are thousands of palm leaf manuscripts in India both in Govt. / Private repositories along with personal domain also. A survey has been made by National manuscript mission, Govt. of India to identify the important Palm leave manuscripts of India available. Out of which “Chikitsa Manjari “ a Palm leaf manuscript of Odisha having 13 copies are found preserved in Odisha state museum, Bhubaneswar with different Individual conditions. Out of them Sl. No Ayurveda/82 as per the accession register of museum has been identified as the only manuscript which has been authorized as “The Manuscript treasure of India“. This paper deals with the detail workout of all the manuscripts available in the museum in the name of Chikitsa Manjari. The documentation of the same is essential in different languages of India for understanding its importance in future as an important manuscript of India & Ayurveda.